To solve the equation \(-8x = 56\):
- Divide both sides by -8: \[ x = \frac{56}{-8} = -7 \]
So, a value of \(x\) that makes the equation true is \(-7\).
Substituting \(-7\) into the equation: \[ -8(-7) = 56 \] When simplified: \[ 56 = 56 \]
Now, let's find a value of \(x\) that makes the equation false. Any value of \(x\) that is not \(-7\) will make the equation false. For example, let's use \(x = 0\).
Substituting \(0\) into the equation: \[ -8(0) = 56 \] When simplified: \[ 0 = 56 \]
Thus:
- A value of \(x\) that makes the equation true is \(-7\), which when substituted into the equation and simplified turns into \(56 = 56\).
- A value of \(x\) that makes the equation false is \(0\), which when substituted into the equation and simplified turns into \(0 = 56\).